STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN PADA SMP NEGERI 2 UNGGUL MESJID RAYA KABUPATEN ACEH BESAR - Sri Banun; Yusrizal .; Nasir Usman (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2016)
Abstract: Strategies appropriate principals are highly demanded to make a change to improve the quality of schools. The purpose of this study to determine the program, program implementation, evaluation and barriers faced by principals to improve the quality of education at the Junior High School 2 Mesjid Raya of Aceh Besar district. The technique of collecting data through observation, interviews, and documentation. Research subjects principals, vice-principals, school committee, chairman MGMPs, teachers and supervisors. Data were analyzed by reducing, display, draw conclusions and verification of data. The results showed: (1) Programs are arranged not entirely based on the consensus reached school personnel. Quality improvement programs documented in the annual program and semester program to be used as a reference in implementing the program. (2) The implementation of the quality improvement program begins with the division of tasks with daily activities forming the executive committee of the school. Programs implemented not entirely based on a predetermined schedule. If the principal is absent, then the authority to implement the program submitted to the vice-principal or a senior teacher. (3) The evaluation was conducted by a committee or team that has been formed by the principal that includes principals, vice principals, supervisors and senior teachers. Prior to the evaluation carried out, the executive committee drafting and preparing instruments evaluation beforehand. The evaluation results will be analyzed and used as a consideration in the decision making in determining the program the following year, and (4) barriers faced by principals are still lacking kediplinan teachers, most school personnel are less committed to the running quality improvement program, the principal less timely in implementing quality improvement programs, the majority of teachers are less serious when seniors do performance monitoring.Keywords: Strategy, Principal and Quality of Education Abstrak:Strategi kepala sekolah yang tepat sangat dituntut untuk melakukan suatu perubahan guna meningkatkan mutu sekolah. Tujuan penelitian ini untuk mengetahui program, pelaksanaan program, Evaluasi dan hambatan-hambatan yang dihadapi kepala sekolah untuk meningkatkan mutu pendidikan pada SMP Negeri 2 Unggul Mesjid Raya Kabupaten Aceh Besar. Teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Subjek penelitian kepala sekolah, wakil kepala sekolah, komite sekolah, ketua MGMP, guru dan pengawas. Data dianalisis dengan cara mereduksi, display, mengambil kesimpulan dan verifikasi data. Hasil penelitian menunjukkan: (1) Program disusun tidak semuanya berdasarkan hasil musyawarah personel sekolah. Program peningkatan mutu didokumentasikan dalam program tahunan dan program semester untuk dijadikan sebagai acuan dalam melaksanakan program. (2) Pelaksanaan program peningkatan mutu diawali dengan pembagian tugas dengan membentuk panitia pelaksana kegiatan harian sekolah. Program dilaksanakan tidak seluruhnya berdasarkan jadwal yang telah ditetapkan. Apabila kepala sekolah berhalangan, maka wewenang pelaksanaan program tersebut diserahkan kepada wakil kepala sekolah atau guru senior. (3) Evaluasi dilaksanakan oleh panitia atau tim yang telah dibentuk oleh kepala sekolah yang meliputi kepala sekolah, wakil kepala sekolah, pengawas dan guru senior. Sebelum evaluasi dilaksanakan, panitia pelaksana evaluasi menyusun dan menyiapkan instrumen terlebih dahulu. Hasil evaluasi akan dilakukan analisis dan dijadikan sebagai pertimbangan dalam pengambilan keputusan dalam menentukan program pada tahun berikutnya, dan (4) Hambatan-hambatan yang dihadapi kepala sekolah adalah kediplinan guru masih kurang, sebagian personel sekolah kurang komitmen dalam menjalankan program peningkatan mutu, kepala sekolah kurang tepat waktu dalam melaksanakan program peningkatan mutu, sebagian guru kurang serius ketika senior melakukan pengawasan terhadap kinerjanya.  Kata Kunci: Strategi, Kepala Sekolah dan Mutu Pendidikan